Ryder - Carroll, Rutter (London : RIBA Publishing, 2012)
Founded in 1953 as Ryder and Yates and now known simply as Ryder, this multi-award winning studio has grown to become one of the largest in the United Kingdom. A varied output of buildings for education, healthcare, interior design, research and manufacturing, residential, and retail and leisure over a period of 60 years has ensured Ryder's position as the North East's leading architectural practice. Richly illustrated with photographs and drawings and featuring text by Ryder partners, this book will explore all aspects of the practice's achievements.
Includes bibliographical references and index.
Keywords: Ryder, Gordon, -- 1919-2000 -- Criticism and interpretation; Architecture -- United Kingdom -- History -- 20th century